PROPOSED PROTOCOL TO ASSIST PEOPLE WITH VENOUS ULCERS - Daniele Vieira Dantas; Rodrigo Assis Neves Dantas; Rhayssa de Oliveira e Araújo; Quinidia Lúcia Duarte de A. Q. Vasconcelos; Isabelle Katherinne Fernandes Costa; Gilson de Vasconcelos Torres (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769211076 Aim: to create a protocol to assist people with venous ulcers (VU) treated at referral hospital of Rio Grande do Norte/RN, Brazil. Method: descriptive and quantitative study at the University Hospital Onofre Lopes. The sample of 39 professionals, the hospital and other institutions of state and Jequie/Bahia. These professionals were judges who selected the guidelines proposed in the literature on VU protocols. After approval by the Research Ethics Committee (Opinion n.º081/07), guidelines were proposals for judges, accepting Kappa(K)≥ 0.81. Results: the proposal contains 11 items: patient/lesion assessment, registry/documentation, care of the wound/skin perilesional, indication of coverage, use of antibiotics and pain treatment, surgical/drug treatment, improvement of venous return/prevention recurrence, patients forwarding, job training and reference/counter-referral. Conclusion: the protocol subsidizes improvements in care for persons with VU, as it guides the multidisciplinary practice.